FACTORS INFLUENCING THE INTENTION TO USE DIGITAL WALLET - Delgertsetseg Delgerjargal, (Journal of Business and Innovation (Бизнес & Инноваци), 2024)
With technology rapidly evolving, society is embracing digital wallets, enabling electronic money transfers across various platforms. Despite growing literature on digital wallets, there’s a research gap in understanding users’ intentions, particularly in developing countries like Mongolia. This study aims to explore factors influencing digital wallet adoption in Mongolia, drawing from behavioral finance principles. Using the Technology Readiness Index and the Technology Acceptance Model, data was collected from 390 users in Mongolia. Findings from Partial Least Squares Structural Equation Modeling reveal that optimism and innovativeness positively impact the intention to use digital wallet, while discomfort and insecurity have a negative effect.